KARAKTERISTIK YAYASAN SEBAGAI BADAN HUKUM DI INDONESIA - Ari Purwadi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
Foundation is a corporation that has particular aim in social, religiousness and humanism sector. Its corporate status is obtained after Ministry of Justice and Human Rights approved its Founding Document. The achievement of its aim and business activity is set based on the Statutes mentioned in the Founding Document which referring to the Foundation Regulation. While it has no members, foundation has components such as Advisors and Foundation Board in which, based on the transparency principles and public accountability, a control mechanism should be held, i.e.: 1. Internal control, by the foundations component named Controller; 2. Annual reports; 3. Audit by Public Accountant; 4. Enquete Right by Attorney General or other concerned parties; and 5. Attorney General authority. As a component in the organization, the foundation board responsible for losses caused by ultra vires action and has a possibility of collective responsibility among the member of the board, or along with the advisor in case of a mistake or a carelessness that leads into a bankruptcy.